METHODS OF THE MODULAR-RATING SYSTEM OF TEACHING AND CONTROL AS A STRATEGY FOR IMPROVING THE MONITORING OF THE LEARNING PROCESS OF STUDENTS - Yunusova , Gulnoza Abduxalikovna (Educational Research in Universal Sciences, 2023)
The modular rating system of teaching and control, which has emerged in the countries of the English-speaking world to a greater extent than the traditional one, is adapted to the conditions that have become new for our pedagogy. The modular learning system is structured in more detail than the traditional one, and the program of educational activities is brought to the students in advance. The purpose of all these classes is to orient the student to an independent in-depth study of this subject in case of interest, otherwise - to give the necessary vital minimum of knowledge on the subject.